The unusual paradox of cancer-associated inflammation: an update - Figueiredo,Cláudia Roberta L. V. (2019)
ABSTRACT The inflammatory response represents a fundamental component of the tumor microenvironment and is responsible for mediating the biological communication network and the molecular signal flow that characterize the neoplastic tissue. Thus, influenced by the inflammatory process, neoplastic and non-neoplastic cells (recruited stromal and circulating cells) interact in a autocrine and paracrine mechanism to control, delineate and model the tumor growth, which is driven by a dynamic mechanism of production of cytokine, growth factors and remodeling enzymes of the extracellular matrix, creating a system of multidirectional influence that, in an accurate analysis, creates a new scientific concept of cancer, now understood as a complex tissue society, in which most of the members cooperate facilitating for neoplasia growth, for the subversion of the immune resistance and favoring metastatic dissemination.